(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Shashi deshpande’s novel roots & shadows explores theinner self of Indu, who symbolizes the new woman who is educated and lives inclose association with society brushing aside all narrow social conventions ofa male –dominated and tradition-bound society. Indu, the protagonist, tries toassert her individuality to achieve freedom which ultimately leads to herconfrontation with her family and society .The novelist, through themaladjustment of Indu, explores the absurdity of the customs and rituals, whichhelp to perpetuate the myth of male superiority.